Demographic pattern and clinical characteristics of optic neuritis in a tertiary eye care centre - Godar, Manita Sunam; Sharma, Ananda Kumar; Thapa, Madhu; Sitaula, Sanjeeta; Gurung, Shanti (Nepalese Journal of Ophthalmology, 2017)
Purpose: To study the demographic pattern and clinical characteristics of optic neuritis cases in a tertiary eye care centre in Nepal. Design: Descriptive, cross-sectional study. Methodology: Complete ocular examination was done in all the newly diagnosed cases of optic neuritis presenting from January 1st 2012 to June 30th 2013. Demographic pattern, clinical features, visual acuity, colour vision, contrast sensitivity and visual field defects were studied. Results: Sixty seven eyes of 50 patients (28 females and 22 males) with optic neuritis were included in the study. The mean age was 34.32 years ± 13.72 years. The male: female ratio was 1:1.27. All the cases presented with complaint of blurring of vision. Painful ocular movement was noted in 58%. On ophthalmoscopic examination around 2/3rd of eyes suffered from papillitis (72%) and 1/3rd from retrobulbar optic neuritis (27%). Only one case of neuroretinitis (1%) was seen in the study. The colour vision pattern was variable. Contrast sensitivity was reduced in 94%. Centrocaecal scotoma was seen in 10.5%. Conclusion: Females were predominantly affected. Unilateral involvement was the most common presenting as papillitis.